2006
DOI: 10.1042/bj20051321
|View full text |Cite
|
Sign up to set email alerts
|

The CD38-independent ADP-ribosyl cyclase from mouse brain synaptosomes: a comparative study of neonate and adult brain

Abstract: cADPR (cADP-ribose), a metabolite of NAD+, is known to modulate intracellular calcium levels and to be involved in calcium-dependent processes, including synaptic transmission, plasticity and neuronal excitability. However, the enzyme that is responsible for producing cADPR in the cytoplasm of neural cells, and particularly at the synaptic terminals of neurons, remains unknown. In the present study, we show that endogenous concentrations of cADPR are much higher in embryonic and neonate mouse brain compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 51 publications
3
31
2
3
Order By: Relevance
“…We have also evidenced robust levels of ADP-ribosyl cyclase activity in cultured PASMCs, using NGD ϩ as an alternative substrate to measure cyclic GDP ribose formation (data not shown), and have, furthermore, shown the expression of CD38 in these cells (this study). The lung is among a group of tissues containing a novel enzyme with ADPribosyl cyclase activity in addition to CD38 (61)(62)(63). This notion is supported by data from CD38 Ϫ/Ϫ mice containing an appreciable amount of cADPR in the lung albeit at lower levels than in the wild type, as well as the fact that cADPR synthesis has been measured in microsomal fraction of PASM homogenates (47,63,64).…”
Section: Discussionsupporting
confidence: 67%
“…We have also evidenced robust levels of ADP-ribosyl cyclase activity in cultured PASMCs, using NGD ϩ as an alternative substrate to measure cyclic GDP ribose formation (data not shown), and have, furthermore, shown the expression of CD38 in these cells (this study). The lung is among a group of tissues containing a novel enzyme with ADPribosyl cyclase activity in addition to CD38 (61)(62)(63). This notion is supported by data from CD38 Ϫ/Ϫ mice containing an appreciable amount of cADPR in the lung albeit at lower levels than in the wild type, as well as the fact that cADPR synthesis has been measured in microsomal fraction of PASM homogenates (47,63,64).…”
Section: Discussionsupporting
confidence: 67%
“…These modifications are shown to increase the recovery of cADPR, improve the functionality of the assay, and reduce between-subject variability (159) . In fact, we observed a significant reduction of brain cADPR despite a difference of only 16% between wildtype and knockout mice, in contrast to the 20% nonsignificant reduction observed by Partida-Sanchez et al (56) and the 18% non-significant reduction observed in Ceni et al (103) . We also observed that levels of NAD þ in the brain were increased by 160 % (148) (P , 0·001) ( Table 4).…”
Section: /2contrasting
confidence: 92%
“…(56) and Ceni et al (103) , who previously measured levels of cADPR in these tissues and found them to be non-significantly decreased. While our levels of brain cADPR are comparable with other published reports, the degree of variability in each group is reduced, which we believe is due to modifications that we have made to the fluorimetric cycling assay for cADPR.…”
Section: /2mentioning
confidence: 89%
“…For this, one reason may reside on cyclase species: the lower expression of CD38 in the pitutitary (Jin et al, 2007a) or contribution of other molecular species, as suggested in the embryonic brain (Ceni et al, 2006). The second possibility is utilization of different G proteins or accessory molecules.…”
Section: Discussionmentioning
confidence: 99%